Penyakit Menular Seksual dengan Sikap Sehat pada Wanita Tuna Susila di Kota Bitung - Tambatjong, Gabrielle E. Ch.; Siagian, Iyone E. T.; Palandeng, Henry M. F. (JURNAL KEDOKTERAN KOMUNITAS DAN TROPIK, 2016)
Sexually transmitted disease is an infection caused by bacteria, virus, parasite or fungi, that transmitted by sexual intercourse. According to the US Centers for Disease Control and Prevention (CDC), there are 6231 Chlamydia trachomatis and Syphilis infected women from 100.000 women in United States. Prevalence of sexually transmited disease in Indonesia was 5608 cases in 2014. The Public Health Department of the City of Bitung reported 959 infected women and 498 infected men, which means more infected women than men. The number of cases increased in 2010-2013 where 1198 were infected and increased to 1429 cases in 2014. The objective of the study was to find out the correlation of sexual transmitted disease knowledge level with healthy intercourse attitude in female prostitute in Bitung city. This study was an analytic descriptive study with cross-sectional method. Population in the study was all female prostitutes in Bitung city. Samples in the study were 75 people as respondents. Data was obtained with a questionnaire and analyzed with chi-square. The result shows that there is a correlation of sexual transmitted disease knowledge level with healthy intercourse behavior, p=0.004 (p<0.01).